Review of Rowan Williams's Passions of the Soul. London: Bloomsbury Continuum - Payton, James R., Jr. (Occasional papers on religion in Eastern Europe, 2024)
A review of Rowan Williams, Passions of the Soul. London: Bloomsbury Continuum, 2024. $15.00 (paperback). ISBN: 978-1-3994-1568-2. 160 pages